2002
DOI: 10.1128/mcb.22.6.1664-1673.2002
|View full text |Cite
|
Sign up to set email alerts
|

RNA Destabilization by the Granulocyte Colony-Stimulating Factor Stem-Loop Destabilizing Element Involves a Single Stem-Loop That Promotes Deadenylation

Abstract: Granulocyte colony-stimulating factor (G-CSF) mRNA contains two distinct types of cis-acting mRNA destabilizing elements in the 3-untranslated region. In addition to several copies of the AU-rich element the G-CSF mRNA also contains a destabilizing region that includes several predicted stem-loop structures. We report here that the destabilizing activity resides in a single stem-loop structure within this region. A consensus sequence for the active structure has been derived by site-directed mutagenesis, revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…While prototype AREs, as in GM-CSF mRNA, reside in a narrow region (50), the more complex situation of IL-6 mRNA is not unique. Studies of G-CSF mRNA identified a destabilizing element adjacent to AREs that forms a stem-loop and prevents mRNA stabilization by the calcium ionophore A23187 (3,46). The sequence and folding of the putative IL-6 mRNA stem-loop are clearly distinct from those in G-CSF mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While prototype AREs, as in GM-CSF mRNA, reside in a narrow region (50), the more complex situation of IL-6 mRNA is not unique. Studies of G-CSF mRNA identified a destabilizing element adjacent to AREs that forms a stem-loop and prevents mRNA stabilization by the calcium ionophore A23187 (3,46). The sequence and folding of the putative IL-6 mRNA stem-loop are clearly distinct from those in G-CSF mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that many individual mRNAs comprise either unpredicted ARE variants or other unknown destabilizing sequences. Even classical AREs are usually imbedded in neighboring sequence elements that are conserved in evolution but differ for each gene (11), and in several cases, such as G-CSF (46), TNF-␣ (53), and endothelin-1 (40), adjacent regions contribute to rapid mRNA degradation.…”
mentioning
confidence: 99%
“…The sequence with 4C, but not that with 3C, could interfere with this stem-loop formation by forming another, although less stable, stem-loop structure involving some of the same nucleotides. Stem-loop structures in the 3'UTR have been shown to be important determinants of message stability in some genes (Putland et al 2002). C-rich sequences are in some cases important for post-transcriptional regulation as exemplified by the α2-globin and collagen α1 genes (Weiss and Liebhaber 1995;Stefanovic et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…7D) at positions 1371-1386. A single stem loop in the 3ЈUTR of granulocyte colony-stimulating factor mRNA has been reported recently to promote deadenylation and destabilization (Putland et al, 2002). Except for this potential stem-loop structure, no known deadenylation or instability elements are contained in this sequence.…”
Section: Discussionmentioning
confidence: 99%